(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of borderline personality disorders among inpatients treated at Institute of Mental Health, Bach Mai Hospital in 2025 and analyze associated factors. Methodology: This cross-sectional study was conducted on 103 inpatients treated at the Institute of Mental Health from February 2025 to July 2025 and used the McLean (MSI-BPD) to classify and assess borderline personality disorders in patients. Results: The prevalence of borderline personality disorder was 41.7%. Inpatient adolescents who have childhood traumas (OR = 3.15; 95% CI = 1.21-8.25; p < 0.01), bully-victimisation (OR = 4.29; 95% CI = 1.23-14.98; p < 0.01), history of alcohol consumption (OR = 5.77; 95% CI = 1.05-31.72; p = 0.03) have a higher rate of screening for borderline personality disorder. Conclusion: The results showed that borderline personality disorder is a disorder that requires attention for subjects coming to specialized psychiatric departments.